Loss of Proteostatic Control as a Substrate for Atrial Fibrillation: A Novel Target for Upstream Therapy by Heat Shock Proteins - Meijering, Roelien A.; Zhang, Deli; Hoogstra-Berends, Femke; Henning, Robert; Brundel, Bianca (Frontiers in Physiology, 2012)
Atrial Fibrillation (AF) is the most common, sustained clinical tachyarrhythmia associated with significant morbidity and mortality. AF is a persistent condition with progressive structural remodeling of the atrial cardiomyocytes due to the AF itself, resulting in cellular changes commonly observed in ageing and in other heart diseases. While rhythm control by electrocardioversion or drug treatment is the treatment of choice in symptomatic AF patients, its effectiveness is still limited. Current research is directed at preventing new-onset AF by limiting the development of substrates underlying AF promotion and resembles mechanism-based therapy. Upstream therapy refers to the use of non-ion channel anti-arrhythmic drugs that modify the atrial substrate- or target-specific mechanisms of AF, with the ultimate aim to prevent the occurrence (primary prevention) or recurrence of the arrhythmia following (spontaneous) conversion (secondary prevention). Heat shock proteins (HSPs) are molecular chaperones and comprise a large family of proteins involved in the protection against various forms of cellular stress. Their classical function is the conservation of proteostasis via prevention of toxic protein aggregation by binding to (partially) unfolded proteins. Our recent data reveal that HSPs prevent electrical, contractile and structural remodeling of cardiomyocytes, thus attenuating the AF substrate in cellular, Drosophila melanogaster and animal experimental models. Furthermore, studies in humans suggest a protective role for HSPs against the progression from paroxysmal AF to persistent AF and in recurrence of AF. In this review, we discuss upregulation of the heat shock response system as a novel target for upstream therapy to prevent derailment of proteostasis and consequently promotion and recurrence of AF.